REKONSTRUKSI PRAKTIK LITERASI DALAM PEMBELAJARAN: STUDI KUALITATIF - Farida Nugrahani; Yuyun Nurmawati; Deti Nurtati; Erlina Catur Purnamasari; Sri Wahyuni; Susilowati; Neni Kustina; Veronika Hevi; Kurniawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the predominance of literacy practices in learning that remain mechanical in nature and provide limited opportunities for students to actively construct meaning. This condition has contributed to low levels of engagement and shallow understanding in the learning process. Therefore, this study aims to explore how the reconstruction of literacy practices in learning occurs and how meaning is constructed through interactions between teachers and students. This research employed a qualitative approach using a case study design. Data were collected through observations, in-depth interviews, and documentation, and were analyzed using the interactive model of Miles includes data reduction, data display, and conclusion drawing. The findings indicate that the reconstruction of literacy practices is characterized by increased student engagement, a shift toward more dialogic interaction patterns, and the development of reflective abilities in understanding and expressing meaning. Literacy practices that were initially focused on technical activities evolved into contextual, participatory, and socially constructed processes. The study concludes that the reconstruction of literacy practices can create more meaningful learning experiences. The implications suggest that teachers need to design interactive and reflective learning environments to enhance the quality of literacy practices.